Numerical Simulation of Water-Sediment Two-Phase Seepage Characteristics and Inrush Mechanism in Rough Rock Fractures - Shi, Xuyang; Li, Ming; Han, Yu; Cai, Qingxiang; Chen, Zhanqing; Chen, Yanlong; Ma, Dan (Frontiers in Physics, 2022)
The water-sediment two-phase flow in the rough fracture is one of the main causes of water-sediment inrush. In this study, numerical simulation models of the water-sediment two-phase flow in the smooth and rough fractures were established by the ANSYS Fluent software based on the seepage theory; mechanical properties of the water-sediment two-phase flow under different conditions were systematically investigated, and the influence laws of the surface morphology of the fracture on the sediment volume concentration, sediment particle size and sediment particle mass density were analyzed. Besides, the influence laws of the sediment volume concentration, sediment particle size and sediment particle mass density on the absolute value of the pressure gradient, the mean velocity of the fluid and the fluid turbulent kinetic energy were also illustrated from the perspective of sediment particle distribution. Research shows that: During the water-sediment flow in the smooth fracture, the absolute value of pressure gradient Gp, the sediment volume concentration Ф, the sediment particle size Dp and the sediment mass density ρp are approximately linear, and the linearity of Gp and Dp is the lowest; During the water-sediment flow in the smooth fracture, the mean velocity v of the continuous-phase fluid rarely changes with Ф, Dp and ρp. However, during the water-sediment flow in the rough fracture, v is greatly affected by Ф, Dp and ρp; During the water-sediment flow in the smooth fracture, the fluid turbulent kinetic energy kt decreases with the increase of ρp and Ф, and decreases with the decrease of ρp. During the water-sediment flow in the rough fracture, kt is significantly affected by Ф, Dp and ρp, which was manifested in the changes of curve shapes and the deviation of the extreme points.